Identification of transcriptional targets of GSK3 involved in glioblastoma invasion. (31st January 2018) - Bruning-Richardson, Anke; Droop, Alastair; Tams, Dan; Boissinot, Marjorie; Hayes, Josie; Cheng, Vinton; Cockle, Julia; Ismail, Azzam; Morton, Ruth; Esteves, Filomena; Mittelbronn, Michel; Lawler, Sean; et al.
Abstract: INTRODUCTION: Glioblastoma multiforme remains one of the most difficult to treat cancers due to the highly infiltrative nature of cancer cells. Targeting the invasive properties of glioblastoma presents a novel treatment avenue. Recently, specific GSK-3 beta (GSK3b) inhibitors such as Bio-Indirubin (BIO), have been described that inhibit the migratory activity of glioma cells. In this study, the GSK-3b downstream targets were investigated. METHOD: Genome-wide transcriptional profiling was used in order to identify GSK3b-driven target genes, and a transcriptional signature for glioblastoma invasion. U251 cells and patient-derived GBM1 cells were treated with the GSK3b inhibitor BIO. Microarray data obtained was mined for deregulated genes with known migratory roles. The up-regulation or down-regulation of candidate genes was confirmed by Western blotting and immunofluorescence. Knockdown of two candidate genes by RNAi, ARHGAP12 and ARHGAP29 was performed, and the effects on invasive properties and characteristics were assessed by 3D spheroid assays, live cell imaging and immunofluorescence, in order to investigate the effects of knockdowns on invasion. RESULTS: We have identified an invasion signature downstream of GSK3b, which includes activators and inactivators of the Rho family of small GTPases. Knockdown of the Rac1 inactivator ARHGAP12 increased migration, whereas knockdown of the RhoA inactivator ARHGAP29 decreased migration as assessed by live cell imaging and 3D spheroid invasion assays. CONCLUSIONS: This study, which for the first time investigates downstream targets of GSK-3b in glioblastoma, has identified an invasion signature which includes regulators of the Rho family of small GTPases. Identified genes will be potential candidates for genetic involvement in glioblastoma progression, and candidate diagnostic and prognostic biomarkers. Candidates will be assessed as potential therapeutic targets.